Being Young in a Fragmented World: A Literature Review on Stress, Alienation, and the Search for Existential Liberation - Peter G. Narsico (Future Science / FSH-PH Publications, 2026)
Applying existential philosophy, in relation to Martin Heidegger’s notions of thrownness, fallenness, and authenticity, the framework provides a hermeneutic insight into what it is to be young in a fragmented world. Instead of synthesizing empirical observations or proposing direct explanations, the review is interpretive and attempts to re‑construct the philosophical and academic work on youth stress, alienation and meaning‑making. The discussion confronts stress and alienation not just as developmental or psychological issues but as existential conditions which disclose conflicts between externally induced demands and young people's ability to form an authentic self‑perception. From literature to scholarship, youth as it transpires across periods not just as a mediatory phase but also as a kind of being‑in‑the‑world involving uncertainty, openness, and a struggle over selfhood. Experiences of disconnection and social pressure may remain widespread but this review underscores how practices of reflection, creativity, and responsibility are part of efforts to live more truthfully in splintered social contexts. By conceptualizing the experience of youth under the existential‑ hermeneutic lens the article also aims to provide a conceptual understanding of youth distress that does not become problem‑ orientated or pathologizing, but rather places youth in the center of meaningful becoming under the conditions of contemporary events.